As técnicas expandidas, figuras e configurações sonoras em L opera per flauto de Salvatore Sciarrino - Onofre, Maria Leopoldina Lima Cardoso (2012)
This study aimed to describe how extended techniques are related to sound settings and the concept of "sound figures" described by Salvatore Sciarrino, used in his pieces for solo flute, published in the book L'Opera per Flauto. Such techniques and figures are fundamental to an understanding of his works. In our analytical reading, we started from the methodological considerations of the composer, described in the book Le Figure della Musica da Beethoven a oggi, which proposes a methodology of analysis based on the concept of "sound figures" - a criteria imported from the visual arts. These sound figures are also present in his compositional works, in a way that they interact with the musical discourse organization. It was sought an understanding of how visual criteria established in its methodology also encompassed the formal considerations of his works for solo flute. So, two different methodologies were used: the qualitative one, based on the theoretical assumptions of the composer; and the quantitative one, based on the spectral analysis of the audio recordings of the pieces. Our goal was to investigate and describe the trajectory of the partial over the time, in order to investigate and demonstrate concepts created by the composer through the proposed analysis.